Pelatihan Pembuatan Silase Pakan Ternak Bagi Kelompok Tani Sedyo Mulyo, Desa Dukuh, Kecamatan Bayat, Klaten - Firmansyah, Hendrix Noviyanto; Widayat, Widi; Syafei, M Hilman Gumelar (Universitas Syiah Kuala, 2024)
Drought severely impacts livestock activities as it becomes increasingly difficult to find green feed for cattle. The hot weather causes the food stock to dry and makes it impossible for cattle to eat. The damage to the cattle food supplies exacerbates this because of termites, especially dry straw. This condition makes the Sedyo Mulyo farmer group worried about the sustainability of cattle food stock. They usually easily get the food stock only from their neighborhood, but because of extreme weather, they have to look for it in areas far from home. Sometimes they also have to buy it if the stock is empty. In response to this problem, it is necessary to preserve cattle food stock when conditions are abundant and use it during the dry season. Cattle food stock preservation is one way to support the conservation of food stock programs. Many methods can be used to preserve cattle food stock today, and the silage method is one of the best of it. Silage is a feed preservation technique with a fermentation process. The purpose of silage is to maintain and reduce the loss of nutrients for future use. This community service program will provide knowledge and training in making this method for cattle food conservation. It is carried out by sharing knowledge sessions and practicing to make silage from greenery and rice straw. The results showed that the Sedyo Mulyo group members had a high understanding of preparing and making silage independently.